A case of laparoscopic distal gastrectomy and median arcuate ligament release for a gastric cancer patient with median arcuate ligament syndrome - Sho Ueda; Masato Maeda; Kenta Nishitani; Tada Seiichiro; Keisuke Kawamorita; Tomoyasu Takayanagi; Toshiki Kobayashi; Yosuke Hashimoto; Kei Yonezawa (Surgical Case Reports, 2022)
Abstract Background The median arcuate ligament syndrome (MALS) is a disease in which the celiac artery is compressed by the arcuate ligament and causes stenosis. If abdominal pain or an aneurysm is observed in the head of the pancreas, it is necessary to release the arcuate ligament, and recently laparoscopic surgery has been reported. However, the indication for treatment in asymptomatic cases is unknown. The treatment for asymptomatic MALS in patients with gastric cancer who are indicated for surgery is also novel. Case presentation A 70-year-old female was found with early gastric cancer in the middle body of the stomach. An enhanced CT scan showed no metastasis, but a gallstone and stenosis of the celiac artery due to the MALS were found. The patient underwent releasing median arcuate ligament after lymph node dissection. A median arcuate ligament was located on the ventral side of the left gastric artery stump, and the celiac artery was exposed when cutting it off. The operation time was 4 h and 59 min, and the bleeding was 6 ml. It took about 5 min to dissect the medial arcuate ligament. The postoperative course was satisfactory, and the patient was discharged 7 days after the operation. CT scan and 3-D CT angiography were performed about 2 months after the operation, and the findings revealed that the celiac artery's stenosis resolved. Conclusion The patient underwent laparoscopic gastrectomy and simultaneously the median arcuate ligament release under an excellent visual field. Therefore, median arcuate ligament release may be considered if MALS is found in a gastrectomy case.